2016
DOI: 10.1080/2150704x.2016.1177242
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the CDOM absorption coefficient in tropical inland waters using OLI/Landsat-8 images

Abstract: Coloured dissolved organic matter (CDOM) is the most abundant dissolved organic matter (DOM) in many natural waters and can affect the water quality, such as the light penetration and the thermal properties of water system. So the objective of this letter was to estimate the CDOM absorption coefficient at 440 nm, a CDOM (440), in Barra Bonita Reservoir (São Paulo State, Brazil) using operational land imager (OLI)/Landsat-8 images. For this two field campaigns were conducted in May and October 2014. During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…A study carried out in the hypertrophic Barra Bonita hydroelectric reservoir located in São Paulo (subtropical Brazilian region), which has a storage capacity of 2.600 hm³ measured aCDOM(440) equal to 1.6 m -1 in May 2014 (end of the wet season) and around 2.8 m -1 in October 2014 (end of the dry season) [60]. In the same study area, Alcântara et al [61] described aCDOM(440) values between 0.6 m -1 (in January 2014) and 1.7 m -1 (in September 2014) for this eutrophic system. Both works related the results to the seasonality with lower CDOM values for the wet season and higher concentration in the dry season.…”
Section: Dynamics Of Cdommentioning
confidence: 89%
“…A study carried out in the hypertrophic Barra Bonita hydroelectric reservoir located in São Paulo (subtropical Brazilian region), which has a storage capacity of 2.600 hm³ measured aCDOM(440) equal to 1.6 m -1 in May 2014 (end of the wet season) and around 2.8 m -1 in October 2014 (end of the dry season) [60]. In the same study area, Alcântara et al [61] described aCDOM(440) values between 0.6 m -1 (in January 2014) and 1.7 m -1 (in September 2014) for this eutrophic system. Both works related the results to the seasonality with lower CDOM values for the wet season and higher concentration in the dry season.…”
Section: Dynamics Of Cdommentioning
confidence: 89%
“…A study carried out in the hypertrophic Barra Bonita hydroelectric reservoir located in São Paulo (subtropical Brazilian region), which has a storage capacity of 2600 hm 3 , measured aCDOM(440) equal to 1.6 m −1 in May 2014 (end of the wet season) and around 2.8 m −1 in October 2014 (end of the dry season) [60]. In the same study area, Alcântara et al [61] described aCDOM(440) values between 0.6 m −1 (in January 2014) and 1.7 m −1 (in September 2014) for this eutrophic system. Both works related the results to the seasonality with lower CDOM values for the wet season and higher concentration in the dry season.…”
Section: Dynamics Of Cdommentioning
confidence: 99%
“…Similarly to our investigation, Alcântara et al [61] tested the potential of the red/blue-green ratio for predicting aCDOM(440) from Landsat-8 images. They also worked in the same hypertrophic reservoir studied by [60], and the best fit was yielded through the red-blue ratio band, derived by in situ hyperspectral remote sensing reflectance (Rrs), at 650 nm (L8 Band 4) and 480 nm (L8 Band 2), i.e., [Rrs(650)/Rrs(480)].…”
Section: Bio-optics and Remote Sensing Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in October, the spectrum exhibited a higher absorption at 410 nm compared to 440 nm. For this month, Alcântara et al (2016a) reported that the Tietê River section before confluence had the highest dissolved organic matter concentrations and, consequently, a CDOM . Thus, the bio-optical status of this section may have led to a different phytoplankton deployment in relation to the rest of the reservoir .…”
Section: Dynamic Of a * φmentioning
confidence: 99%